"I'm smiling back at you": Exploring the impact of mask wearing on communication in healthcare. Issue 1 (10th October 2020) - Marler, Hollyanna; Ditton, Annabel
Abstract: Background: Surgical and respirator masks are worn to reduce the risk of droplet and airborne transmission of viral respiratory disease. As a result of the novel coronavirus (COVID‐19) pandemic, mask wearing has been designated mandatory for healthcare professionals working in UK hospitals for the foreseeable future. It is thus timely to consider the long‐term implications of mask wearing on communication within healthcare settings, from both a patient and a clinician perspective. Aims: The primary objective is to identify research evidence that corresponds to the mask‐wearing experiences of healthcare professionals working on the ground. By drawing together a summary of the literature illustrating the potential challenges associated with mask wearing, it is possible to make an application to various clinical cohorts and to formulate a set of preliminary, evidence‐based support strategies. The paper additionally explores the role for the Speech and Language Therapist (SLT) in supporting communication in the context of mask wearing. Methods & Procedures: Through a scoping review of the relevant literature, this paper reflects holistically on the prospective challenges associated with mask wearing across a variety of healthcare settings and patient populations. The subsequent conclusions have been used to inform the proposed clinical guidelines for safe and effective practice. Outcomes & Results: There is a current research gap with regards to mask wearing in non‐medical and non‐clinical healthcare workers, and the impact this may have on both a professional and a personal basis. In the absence of preliminary data, the development of associated communication support strategies is hindered. This paper draws upon a variety of clinically conceivable issues faced by healthcare professionals, outlines important practical and ethical considerations, and proposes evidence‐based solutions to some of the challenges identified. Future research is required to gather evidence with regards to actual clinical experiences of mask wearing to substantiate hypotheses. Conclusions & Implications: Although undoubtedly essential in protecting the health of staff and patients, there are numerous logistical, physiological, psychological, social and economic complications associated with the wearing of masks. The ability of healthcare staff to successfully communicate with patients and with colleagues is jeopardized, which may adversely affect the efficiency, effectiveness, equitability and, most notably, safety of therapeutic intervention. The SLT has a distinct role in facilitating communication in order to safeguard the provision, accessibility and efficacy of services. What this paper adds: What is already known on the subject: Existing research explores the impact of mask wearing on medical doctors, surgeons and dentists, and upon the corresponding patient cohorts. Little is known about how mask wearing may affect Allied Health Professionals and their ability to deliver therapeutic interventions safely and effectively. With mandatory face covering potentially a long‐term requirement for UK healthcare staff, it is both timely and relevant to consider the consequences of mask wearing on communication across acute and community settings. What this paper adds to existing knowledge: This paper identifies a range of prospective key issues associated with mask wearing across a variety of clinical and non‐clinical populations, with application specifically to vulnerable patient cohorts. Through evidence synthesis, this paper provides a summary of fundamental issues supported by relevant literature, and draws upon these in order to propose a preliminary set of evidence‐based clinical guidelines setting out potential solutions to the challenges faced. This review additionally assists in quantifying the role of the SLT within these extraordinary circumstances, with the aim of prompting unified practice, building upon professional guidance and increasing skill recognition. What are the potential or actual clinical implications of this work?: In addition to their role in facilitating the development of individualised communication strategies for patients, SLTs should actively seek to provide widely accessible multidisciplinary education opportunities focusing on supporting communication; with specific reference to mask wearing and the associated communicative challenges. At a commissioning and managerial level, leaders within healthcare should acknowledge mask wearing as just one of the complexities associated with frontline working in the context of the COVID‐19 pandemic, and aim to support their workforce by delivering resources and protocols which maximize and promote staff safety, efficiency, resilience and well‐being in concurrence with positive patient outcomes.